O ensino introdutório da teoria da endossimbiose sequencial a luz da teoria da complexidade na educação de jovens e adultos, no município de Alta Floresta, MT - Henicka, Gracieli da Silva (2015)
Researches show that the inclusion of concepts related to Complexity Theory (CT) is feasible in high school. The overall objective of this study was to investigate the feasibility and difficulties in the teaching-learning process of the concepts and principles of the Theory of Sequential Endosymbiosis (TSE) at the light of CT deriving from an educational product reasoned in the principles of the Theory of Meaningful Learning. The work is based also on Kuhn’s, Maturana’s and Varela’s epistemology. This research investigated the previous knowledge of students of the second year of high school of the Youth and Adult Education (EJA) about the concepts ecology of evolution, General Biology and Genetics. Such Concepts showed potential to anchor the new concepts related to TES by Lynn Margulis, which were covered below. At the end of the survey a teacher's guide with directions and issue of deepening suggestions has been created by way of educational product, still containing three presentations in PPTX, three texts-support for the teacher, three texts-support for the student and seven tests. The material will be available on the program website (http://fisica.ufmt.br/pgecn/) and researcher (www.alegriaeciencia.com.br). The methodology was qualitative and quantitative with participant observation. The research took place in Alta Floresta, MT and was organized in five meetings between March 19th 2014 and April 16th 2014. The participants were 94 students of EJA, 37 of the 2nd year from night shift, 32 of the 2nd year from morning shift and 27 the 2nd year from the afternoon shift. The morning shift group showed on average, excluding the interview, 66.51% attendance in the activities of research, the evening shift group 64.55% and the night shift group only 44.40%. The analysis of all the groups together showed 57.44% average rate, suggesting that students skipped many of the meetings, especially the students of the night shift. Only 77 students answered the pretest A which investigated the profile of the students. Of these, 63.64% are women and 36.36% are men. In analyzing the courses of the daytime, this scenario is repeated, but it is not the case of the night shift group, where most are men aged 18-22 years old, while the age group of students of the daytime is more diverse, with the presence students up to 62 years old. Regarding personal aspirations most students in each class demonstrated intention to complete high school and continue on their training, making technical courses and/or college. In general, the results from the workshops pointed to some difficulties in reading and interpreting of students hampering the learning, but also point advances in the evolution of learning, there was a good evidence of uptake of conceptual meanings that can be considered significant precursors to some e-learning concepts. This study demonstrated that it is feasible to insert Theory of Sequential Endosymbiosis at the light of Complexity Theory in high school of EJA.